Integral Awareness of the World (2010)
Having an integral awareness of the world implies not only an attitude of attention, care and preservation of oneself, but also an active attitude of construction with the environment, a call to the ability to transform what exists. EAFIT Children's University is marked by diversity. We want to be aware that the world is populated by diverse beings.